Mechanisms and Advances of Epigenetic Regulation in Cardiovascular Disease - Xiaojun Wang; Xusheng Teng; Chao Luo; Laifa Kong (Frontiers in Bioscience-Landmark, 2024)
Epigenetics refers to heritable changes in gene expression and function that impact nuclear processes associated with chromatin, all without altering DNA sequences. These epigenetic patterns, being heritable traits, are vital biological mechanisms that intricately regulate gene expression and heredity. The application of chemical labeling and single-cell resolution mapping strategies has significantly facilitated large-scale epigenetic modifications in nucleic acids over recent years. Notably, epigenetic modifications can induce heritable phenotypic changes, regulate cell differentiation, influence cell-specific gene expression, parentally imprint genes, activate the X chromosome, and stabilize genome structure. Given their reversibility and susceptibility to environmental factors, epigenetic modifications have gained prominence in disease diagnosis, significantly impacting clinical medicine research. Recent studies have uncovered strong links between epigenetic modifications and the pathogenesis of metabolic cardiovascular diseases, including congenital heart disease, heart failure, cardiomyopathy, hypertension, and atherosclerosis. In this review, we provide an overview of the progress in epigenetic research within the context of cardiovascular diseases, encompassing their pathogenesis, prevention, diagnosis, and treatment. Furthermore, we shed light on the potential prospects of nucleic acid epigenetic modifications as a promising avenue in clinical medicine and biomedical applications.